Kajian produktivitas alat berat pada proyek pembangunan gedung Kantor PKK, Dekranasda dan UMKM Center Kota Makassar - Rasyid, Muhammad Asdar; Hadi, Abd Karim; Supardi, Sudarman (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The construction project of the PKK Office Building, Dekranasda, and UMKM Center in Makassar City has a strategic role in supporting economic growth and improving public services. The purpose of this study was to analyze the productivity of heavy equipment used in this work. The results showed that the excavator and mobile crane heavy equipment in the 8th year, the truck mixer in the 5th year, while the dump truck and concrete pump in the 4th year, each had a value smaller than per year. Productivity analysis showed that the Komatsu PC 200 Excavator heavy equipment had a total cycle time of 11 minutes, the 4 m³ type Dump Truck was more efficient with a cycle time of 5.6 minutes compared to the 8 m³ type, and the XCMG QY25K Mobile Crane showed high efficiency with a total cycle time of 3.124 minutes. Meanwhile, the Truck Mixer had the longest cycle time, which was 136.7 minutes, so it requires better time management